Video-on-demand for enhanced learning using power point - Aw, Chun Hong (2011)
A2115-101 Video-on-Demand for Enhanced Learning using PowerPoint.This report summary what the student have learnt and done during the Final Year Project (FYP) period that span across two semesters. The FYP Program had given the student a chance to make use of the knowledge and skills that were taught in the University. The student has chosen a project titled Video-on Demand for Enhanced Learning using PowerPoint. In this project, the student has made use of Visual Basic, Microsoft Access and PowerPoint to accomplish the requirements. Visual Basic was used as the fundamental language to create a media player user interface, thereafter implementing a database for storing the various segments information. With these concepts, the student was able to integrate them into PowerPoint. The report has also documented on the problems and solutions that were encountered during the completion of the project. Lastly, the student has proposed several improvements that can be realized to better enhance the performance.